2014
DOI: 10.1590/s0034-737x2014000200007
|View full text |Cite
|
Sign up to set email alerts
|

Teste de envelhecimento acelerado em sementes de crambe (Crambe abyssinica Hochst), cultivar FMS Brilhante

Abstract: Accelerated aging test in seeds of crambe (Crambe abyssinica Hochst), cultivar FMS BrilhanteThe use of high physiological quality seeds is essential in the establishment of any crop. Germination and vigor tests are required for seed quality control. The objective of this study was to evaluate the efficiency of the accelerated aging test in determining the vigor of crambe seeds. The initial quality of five lots of crambe seeds, cultivar FMS Brilhante, was assessed by determining the water content, germination, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 10 publications
2
6
0
2
Order By: Relevance
“…In addition, seeds in this treatment showed delayed germination, with a lower germination speed index. Amaro et al (2014) analysed five lots of crambe seeds and obtained an average germination of 42%, indicating that crambe seeds have a low germination percentage, which was also observed in this study. This relates to the fact that crambe seeds are characterised by post-harvest dormancy, resulting in a low germination percentage when compared to other agricultural seeds (Costa et al, 2012;Oliveira et al, 2014).…”
Section: Resultssupporting
confidence: 81%
“…In addition, seeds in this treatment showed delayed germination, with a lower germination speed index. Amaro et al (2014) analysed five lots of crambe seeds and obtained an average germination of 42%, indicating that crambe seeds have a low germination percentage, which was also observed in this study. This relates to the fact that crambe seeds are characterised by post-harvest dormancy, resulting in a low germination percentage when compared to other agricultural seeds (Costa et al, 2012;Oliveira et al, 2014).…”
Section: Resultssupporting
confidence: 81%
“…Our results verified that the exposure of the seeds of passion fruit to aging at 43ºC for 72 h did not influence the germination of the unripe seeds but there was a significant difference between the unaged and aged seeds of the sweet passion fruit, collected at medium altitudes. Previous studies showed that aging at 43 °C in the 48, 72, and 96 h periods promoted an increase in the percentage of germination in the seeds of Crambe (Amaro et al, 2014). A significant difference in vigor was also observed between the unaged and aged seeds in our study (Table 3).…”
Section: Physiological Quality Of the Seeds Of Passion Fruitsupporting
confidence: 81%
“…This suggests that this test has sensibility limitations for separating seed lots by their physiological potential (Amaro et al, 2014). Thus, Marcos-Filho (2015b) also reinforces the importance of using more than one test to estimate seed vigor, due to the variation of efficiency of the available procedures.…”
Section: Resultsmentioning
confidence: 88%